Hubungan Pola Asuh Orang Tua Dengan Tumbuh Kembang Anak Pra Sekolah (JURNAL KEPERAWATAN, 2022)
Parenting is a relationship between parents and their children, through parenting parents intend to stimulate their children as a form of parenting efforts and carefor children so that children grow and develop optimally. If it is not immediately addressed, the child's development will be hampered and result in malnutrition, stunting, and ignorance. The aim is to find out the relationship between parenting style and pre-school child development in Diniyah Pekanbaru. The method of this study was descriptive analytical with a cross sectional approach, with a sample of 44 respondents in parents and children aged 4-6 years. In this study, researchers used questionnaires, measurements of body weight and height and KPSP observation sheet. The statistical test used is the chi square test. Results arenting good (democratic) as many as 30 respondents, the growth of normal children as many as 28 children, child development according to as many as 30 children. The results of bivariate analysis showed a relationship between parenting style and growth (p = 0.022) and development (p = 0.04). The conclusion is that there is a relationship between parenting style and pre-school child development in Diniyah Pekanbaru